STUDY ON THE ROLE OF EMPLOYEES WORKING DISCIPLINE PENGAWASANDALAM RANGKAPENINGKATAN (CASE STUDY IN THE OFFICE OF MARINE AND FISHERIES DEPARTMENT EAST DISTRICT KUTAI). - Ridhawati, Ridhawati (PREDIKSI, 2016)
Human civilization is growing every time. Humans as social beings are not biased off to live alone in public life. Along with the growing civilization and the need to live with other human beings, human beings are driven to have an association. The society as a place of various human activities in order to achieve certain goals. Society is called organization. The relationship between humans and the organization very closely. Humans require organizations to meet their needs. For example, humans require schools, sports clubs, religious associations, associations of music. While organizations need humans as a driving factor. Activities of the organization will not be separated from the human factor. Factors life and death of the organization in achieving its goals depends on the involvement and activity of man. Every organization operates using resources to produce goods or services that can be marketed. Management of these resources have an impact on the achievement of business objectives. Source the power of the organization, among others, financial / capital, physical / material, technological and human. These resources must be used optimally as possible and so the goal is reached. In a private company or government agency, people who carry out the duties and obligations referred to by employees. Given the importance of the position of employees in an organization, then the implementation of the activities necessary qualified staff in their ability, strong will, appreciate the time, high loyalty for the organitations, can carry out it’s obligations to the organization's interest above personal interest and being disciplined in work. An organization would not want an employee who works as good as him but wants employees who work diligently followed a high work discipline. In connection with the foregoing, that the goals of the organization that has been planned to be achieved, then the employee should be directed in accordance with the objectives of the organization. So expect the employee can do his job in accordance with a predetermined and does not deviate from the provisions / regulations that have been made. To still be able to know the implementation of the activities carried out so that employees do not deviate from the provisions / regulations required the existence of a real action. The real action is with their supervision.